Let the day perish The nexus of personification and mythology in Job 3 - Leonard, Jeffery M (2018)
While both Job 3 and Jeremiah 20 contain curses against the day of one's birth, the language of Job's curses resonates more forcefully than does Jeremiah's. In this study, I argue that the feature which lends Job such extraordinary power is not only the author's dramatic use of personification but specifically the author's personification of the mythologically potent figures, day and night. Among Israel's ancient neighbors, day and night were regularly regarded as deities. While Israel does not appear to have followed suit in divinizing these two, the author of Job does take advantage of their mythological background to heighten the personal nature of the entities the suffering patriarch curses. Job's treatment of night and day reveals an important nexus between personification and mythology and sheds light on other, similar examples of personification in the Hebrew Bible.
Keywords: Bibel; Cursing; Jeremiah 20; Job 3; Day; Mythology; Night; Personification